How Bone Connects Life’s Past to the Present. Zooarchaeology at Dadan (AlUla, Saudi Arabia) - Hervé Monchot; Anaïs Marrast; Agata Strzelecka-Misonne (Open Quaternary)
The excavations undertaken on the site of Dadan have recovered a very important bone assemblage (more than 167,696 remains), allowing us to reconstruct and better understand the subsistence strategies of the inhabitants in a central part of the al-‘Ula (AlUla) oasis for at least three thousand years. The city of Dadan was the capital of important Iron Age regional powers, the Dadan and later the Lihyan Kingdoms, which controlled the caravan routes across the oasis between the Levant and Mesopotamia and the south of the Arabian Peninsula, and later the Red Sea. Subsequently, the site of Dadan continued to be occupied in the Late Antique and Islamic periods. From these different chronological periods and excavation areas, the bone remains, representing meal leftovers, shows a clear dominance of caprine (sheep/goat) followed by the Arabian camel. Wild species, such as gazelle, oryx and hare, signs of hunting activities, are very rare, as also is birdlife. These domestic species are certainly the result of local breeding and underline the great autonomy of the inhabitants of the oasis. Only fish or seashell come from a more distant horizon, the Red Sea via the trade routes. The absence of pigs and the lack of chicken or cattle raise many questions, as does the small presence of camel in the area occupied/developed in the Late Antique.